Defining appropriate government strategies to reduce unemployment during COVID-19 pandemics - Kalkavan, Hakan; Baş, Halim; Ersin, İrfan; Eti, Serkan; Yüksel, Serhat (Springer Science and Business Media Deutschland GmbH, 2021)
The unemployment problem became more significant, especially after COVID-19 pandemics. This situation affected both developing and developed countries in a negative manner. Hence, the policies implemented by the states to prevent unemployment were also carefully considered during this process. Within this scope, various suggestions of ILO and OECD institutions have been made regarding these strategies. This study aims to identify the significant strategies countries should develop to reduce unemployment. For this purpose, 10 basic strategies offered by OECD to reduce the unemployment problem are considered. Moreover, an evaluation has been carried out by considering fuzzy DEMATEL methodology. The findings demonstrate that ensuring adequate income protection is the most appropriate criterion to minimize the unemployment problem in the COVID-19 process. During the pandemic period, economic rescue packages were announced by many governments and institutions. Despite all this support, millions of people lost their jobs in this process. Considering the analysis results obtained in this study, it would be appropriate for governments to focus primarily on the unemployed. In this framework, the implementation of strategies that will prevent citizens from being unemployed will contribute to the solution of this problem. Despite all these efforts, there may still be people losing their jobs in this process. Therefore, income-generating policies should be implemented especially for these people. For this purpose, the duration of unemployment benefits may be extended. In this way, it will be easier to combat the unemployment problem caused by the COVID-19 pandemic.
Keywords: COVID-19; Pandemics; Government Strategies; Unemployment